Molecular Imaging of endometrial sentinel lymph nodes utilizing fluorescent-labeled Tilmanocept during robotic-assisted surgery in a porcine model - Anderson, Kristen M.; Barback, Christopher V.; Qin, Zhengtao; Hall, David J.; Hoh, Carl K.; Vera, David R.; McHale, Michael T. (PloS one, 2018)
Molecular imaging with a fluorescent version of Tilmanocept may permit an accurate and facile detection of sentinel nodes of endometrial cancer. Tilmanocept accumulates in sentinel lymph nodes (SLN) by binding to a cell surface receptor unique to macrophages and dendritic cells. Four female Yorkshire pigs underwent cervical stromal injection of IRDye800-Tilmanocept, a molecular imaging agent tagged with near-infrared fluorescent dye and radiolabeled with gallium-68 and technetium-99m. PET/CT scans 1.5 hours post-injection provided pre-operative SLN mapping. Robotic-assisted lymphadenectomy was performed two days after injection, using the FireFly imaging system to identify nodes demonstrating fluorescent signal. After removal of fluorescent nodes, pelvic and periaortic node dissections were performed. Nodes were assayed for technetium-99m activity, and SLNs were established using the "10%-rule", requiring that the radioactivity of additional SLNs be greater than 10% of the "hottest" SLN. Thirty-four nodal samples were assayed ex vivo for radioactivity. All the SLNs satisfying the "10%-rule" were detected using the FireFly system. Five fluorescent nodes were detected, corresponding with preoperative PET/CT scan. Three pigs had one SLN and one pig had two SLNs, with 100% concordance between fluorescence and radioactivity. Fluorescent-labeled Tilmanocept permits real-time intraoperative detection of SLNs during robotic-assisted lymphadenectomy for endometrial cancer in a porcine model. When radiolabeled with gallium-68, Tilmanocept allows for preoperative localization of SLNs using PET/CT, and shows specificity to SLNs with persistent fluorescent signal, detectable using the FireFly system, for two days post-injection. In conclusion, these findings suggest that a phase I trial in human subjects is warranted, and that a long-term goal of an intra-operative administration of non-radioactive fluorescent-labeled Tilmanocept is possible.